A novel approach using optical fringe analysis for breast carcinoma detection / Rajendaran A/L Vairavan. - Vairavan, Rajendaran (School of Microelectronic Engineering, Universiti Malaysia Perlis, 2017)
The prime objective of this study is to explore the feasibility of using an optical method based on phase shift digital fringe projection technique to analyze and assess the breast surface changes due to abnormal lump within the breast for the application of early detection of breast carcinoma. To achieve the main objective, the following supplementary objectives was set ; to study the existing breast carcinoma detection modalities with particular focus placed on non-invasive techniques ; to model the breast with suitable constraint settings and to perform simulation analysis of this model with a suitable analysis approach that will analyze the stress on the breast skin surface due to the presence of a lump within the breast ; to design a digital fringe projection rig comprising of projection rig, projection unit, an image acquisition unit and processing/analysis unit ; to assess the breast surface changes due to the presences of abnormal lump using the digital fringe projection rig through a few sets of experimental analysis.